Analysis of Reaction-Diffusion Models with the Taxis Mechanism - Ke, Yuanyuan (Financial Mathematics and Fintech, 2022)
This open access book deals with a rich variety of taxis-type cross-diffusive equations. Particularly, it intends to show the key role played by quasi-energy inequality in the derivation of some necessary a priori estimates. This book addresses applied mathematics and all researchers interested in mathematical development of reaction-diffusion theory and its application and can be a basis for a graduate course in applied mathematics.